Profil Berpikir Kritis Siswa Kelas VIII SMPN 7 Palu dalam Menyelesaikan Masalah Terkait Teorema Pythagoras Ditinjau dari Kemampuan Matematika - Rizky Arlius Pokote; Fajriani; Pathuddin; Ibnu Hadjar (Lembaga Intelektual Muda (LIM) Maluku, 2026)
Critical thinking is an important competency in mathematics learning, but many students still experience difficulties in solving problems, especially on the Pythagorean theorem. This study aims to describe the critical thinking profile of eighth-grade students at SMP Negeri 7 Palu in solving Pythagorean theorem problems in terms of mathematical ability. The study used a descriptive qualitative approach with two subjects, namely one student with high mathematical ability (IR) and one student with medium mathematical ability (MN), who were selected purposively based on the results of a mathematical ability test. Data were collected through a mathematical ability test, a Pythagorean theorem problem-solving test, and in-depth interviews to reveal students' thinking processes. Data analysis was carried out through the stages of data reduction, data presentation, and drawing conclusions by referring to the six FRISCO critical thinking indicators according to Ennis, namely focus, reason, inference, situation, clarity, and overview. The results showed that students with high mathematical ability were able to optimally fulfill all FRISCO indicators, while students with medium ability only fulfilled some of the indicators and tended to rely on one solution procedure. These findings indicate that mathematical ability influences the quality of students' critical thinking, so that learning that encourages the use of various problem-solving strategies is needed to develop critical thinking skills more optimally.